Translating the “City of the Eye”: Mapping Contemporary Venice between Travel Writing and Residents’ Accounts - Marinetti, Cristina (Text Matters: A Journal of Literature, Theory and Culture, 2025)
In this article I explore the “translational city” through the unique lens of contemporary Venice. The multiple cities that have been the subject of work on the “translational city” display different linguistic and cultural relations: from the dual city, through (post)colonial cities, to cosmopolitan cities. While Venice historically shares some of the characteristics of these models, its social, cultural, and linguistic make-up is exceptional in terms of both nature and scale. Progressive hyper-touristification in the last 30 years has led to a complete transformation of Venice as an urban space with the dramatic shrinking of the resident population and their ways of inhabiting the city and has made travel writing central to how its urban spaces are imagined and experienced. This shift calls for a reconsideration of the role of travel writing in shaping our perceptions and our experiences of the city. The article offers a comparative analysis of how the city is imagined, by placing Joseph Brodsky’s influential English travel account, Watermark, in conversation with two collections of residents’ narratives; it is also an attempt to map how travel writing, as a form of translation, mediates between the city’s global perceptions and its local realities. The analysis uncovers an important disjuncture between how Venice is imagined by Brodsky as a global citizen and how it is remembered, memorialised, and constructed by Venetian residents as “denizens” seeking to reconstitute a local/minoritised language. The article explores Venice as a specific example of a translational city, while reflecting on a broader set of questions on the politics of language, travel, translation, and community.